Macrophage activation syndrome-like in multiple myeloma patients treated with the academic CAR-T against BCMA ARI0002h - Munárriz, Daniel; Rodríguez-Lobato, Luis Gerardo; López-Corral, Lucía; Arnaldos-Pérez, Cristina; Cabañas, Valentín; López-Muñoz, Nieves; Oliver-Caldés, Aina; Ponce, Juan Carlos; Reguera, Juan Luis; Martín, Ana África; Martínez-Cibrián, Núria; Tovar, Natalia; et al. (Frontiers in Immunology, 2025)
BackgroundChimeric antigen receptor T-cell (CAR-T) therapy targeting B-cell maturation antigen (BCMA) has revolutionized multiple myeloma treatment (MM). However, managing its immune-mediated adverse events, particularly macrophage activation syndrome-like (MAS-like), remains challenging due to underreporting.MethodsThis multicentre, retrospective, analytical study evaluated MM patients treated with the anti-BCMA academic product ARI0002h. MAS-like was defined using the University of California San Francisco (UCSF) consensus criteria. Primary endpoints included baseline characteristics, predictive factors, and survival outcomes associated with MAS-like.ResultsOf 80 patients, 12 (15%) met the UCSF criteria for MAS-like. These patients presented higher ISS scores (ISS III: 54.5% vs. 15.2%; p = 0.006), elevated serum monoclonal components (31.3 g/L vs. 6.8 g/L; p = 0.004), and a higher prevalence of extramedullary disease (41.7% vs. 16.2%; p = 0.057). MAS-like typically emerged 9 days post-infusion, with elevated ferritin, followed by LDH (median 11.5 days) and hypofibrinogenemia (median 14 days). One-third of patients met all UCSF criteria, and all exhibited hypertriglyceridemia, hypertransaminasemia, and cytopenias. Histopathological examination was positive in 63% of evaluated patients. Patients who developed MAS-like had poorer responses (CR: 25% vs. 68%; p = 0.008) and shorter median PFS and OS (7 months vs. 21.4 months and 18 months vs. not reached, respectively; p = 0.004). Those meeting all UCSF criteria had even inferior outcomes.ConclusionsMAS-like is associated with poorer responses, reduced PFS and OS, especially in patients meeting all UCSF criteria. High tumour burden, including elevated monoclonal component, high ISS and extramedullary disease, seems to contribute to MAS-like development.